Association of CCL2 with systemic inflammation in Schnitzler syndrome. (1st April 2019) - Krause, K.; Sabat, R.; Witte‐Händel, E.; Schulze, A.; Puhl, V.; Maurer, M.; Wolk, K.
Summary: Background: Schnitzler syndrome (SchS) is a rare autoinflammatory disease characterized by urticarial exanthema, bone and joint alterations, fever and monoclonal gammopathy, which manifest mostly in the second half of life. It involves overactivation of the interleukin (IL)‐1 system, but the exact pathophysiological pathways remain largely unknown. Objectives: To identify and characterize the pathogenetic players in SchS. Methods: Blood parameters were quantified in patients with SchS compared with healthy controls and patients with psoriasis and hidradenitis suppurativa using enzyme‐linked immunosorbent assay (ELISA). CCL2 expression in cultured primary cells was analysed by quantitative reverse‐transcriptase polymerase chain reaction and ELISA. Results: CCL2, a chemoattractant for monocytic and further mononuclear immune cells, was found to be significantly elevated in patients with SchS. CCL2 levels showed a positive association with global disease activity, especially with bone pain, but not disease duration, gammopathy, neutrophilia or skin disease. In vitro stimulation assays demonstrated a strong CCL2 production capacity of mononuclear immune cells and fibroblasts, but not epithelial or endothelial cells. Among a range of inflammatory mediators, only IL‐1β (immune cells, fibroblasts) and tumour necrosis factor (TNF)‐α (fibroblasts) were important CCL2 inducers. TNF‐α, but not IL‐17, strengthened the CCL2‐inducing effect of IL‐1β in fibroblasts. Accordingly, CCL2 levels positively correlated with both TNF‐α and IL‐1β serum levels in patients with SchS. Therapeutic IL‐1β blockade decreased CCL2 blood levels in these patients as early as 1 week after the initiation of treatment. Conclusions: CCL2 may be an important component of the pathogenetic cascade leading to bone alterations, and a suitable marker of disease activity in patients with SchS.